Atypical forms of employment among young people in the European Union - Oliveira, Luísa (2016)
The article analyses precarious work among the young people in the 27 EU member states. It seeks to contribute to an understanding of the conditions relating to the integration of young people into the labour market in three decades (precisely, in 1988, 1998 and 2008), from a perspective that compares the countries. The information is derived from Eurostat sources; as its central indicator it takes the rate of temporary work and the interrelations between the young people’s qualification levels and the reasons cited for being in temporary work. A multivariate analysis was carried out: principal components analysis for categorical data (CatPCA). This allows us to present the differences between European Union countries, as well as the link between education and labour-market integration processes.